Digital Journalism and the Revitalization of Nusantara Languages: Integration of Natural Language Processing, Blockchain, and Digital Ethics for Linguistic Preservation - M. Yoserizal Saragih (Ikatan Sarjana Komunikasi Indonesia, 2025)
In the ever-evolving digital era, regional languages ​​in Indonesia are facing the threat of extinction due to modernization and globalization. This study aims to explore the role of digital journalism supported by artificial intelligence (AI), natural language processing (NLP), and blockchain technology in preserving Nusantara languages. The method used is descriptive analytical by reviewing literature from indexed scientific journals, UNESCO reports, and case studies related to language preservation and digital technology. The results of the study show that digital journalism plays an important role in documenting and disseminating regional languages ​​through interactive formats such as videos, podcasts, and multimedia articles, which are more attractive to the younger generation. NLP technology helps analyze, translate, and build linguistic models of regional languages, facilitating the processing and distribution of multilingual content. In addition, the development of regional language-based chatbots opens up opportunities for fun interactive learning. On the other hand, blockchain ensures the authenticity and copyright protection of language content by permanently and encryptedly recording each documentation, and enables cultural tokenization to encourage active participation of local communities. This study confirms that the integration of digital journalism, NLP, and blockchain not only strengthens efforts to preserve regional languages, but also builds an ethical, transparent, and sustainable digital ecosystem. Collaboration between journalists, local communities, and technology developers is the key to success in ensuring that Nusantara languages ​​remain alive and relevant in the modern era.